“… wood carved by the knife of circumstance…”? : Cape rapists and rape in South Africa, c. 1910-1980 - Fransch, Chet James Paul (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.